Characterization of Novel Reassortant Influenza A (H5N2) Viruses Isolated from Poultry in Eastern China, 2015 - Wu, Haibo; Lu, Rufeng; Peng, Xiuming; Peng, Xiaorong; Cheng, Linfang; Liu, Fumin; Wu, Nanping (Frontiers in Microbiology, 2017)
Recently, novel variants of H5 highly pathogenic avian influenza viruses have been frequently isolated from poultry and wild birds in Asia, Europe and North America. Live poultry markets (LPMs) play an important role in the dissemination of influenza viruses. Four H5N2 avian influenza viruses (AIVs) were isolated from poultry during surveillance of AIVs in LPMs in Eastern China, in 2015. Whole-genome sequencing, combined with phylogenetic and antigenic analyses were performed to characterize these viruses. These H5N2 viruses had undergone extensive reassortment resulting in two genetic groups of viruses in poultry. These viruses exhibited slightly pathogenicity in mice, and replicated without prior adaptation. The continued circulation of these novel H5N2 viruses may represent a threat to human health.